2011
DOI: 10.1165/rcmb.2009-0427oc
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Induces Translocation of IL-6 from the Lung to the Systemic Circulation

Abstract: The biological mechanisms responsible for an association between elevated concentrations of ambient particulate matter (PM) and increased cardiovascular morbidity and mortality remain unclear. Our laboratory showed that exposure to PM induces systemic inflammation that contributes to vascular dysfunction. This study was designed to determine whether the lung is a major source of systemic inflammatory mediators, using IL-6 as a surrogate marker. We also sought to determine the impact on vascular dysfunction aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 52 publications
6
81
0
5
Order By: Relevance
“…Similar results were seen after a single dose and repeated dose administration of particles [8,[26][27][28]. Studies by Nemmar et al [26] in humans showed doi: 10.7243/2055-091X-5-2 an increase in a number of mast cells and neutrophils in the bronchial submucosa along with an increase in myeloperoxidase and interleukin 8 (IL-8) concentrations.…”
Section: Discussionsupporting
confidence: 59%
“…Similar results were seen after a single dose and repeated dose administration of particles [8,[26][27][28]. Studies by Nemmar et al [26] in humans showed doi: 10.7243/2055-091X-5-2 an increase in a number of mast cells and neutrophils in the bronchial submucosa along with an increase in myeloperoxidase and interleukin 8 (IL-8) concentrations.…”
Section: Discussionsupporting
confidence: 59%
“…The generation of a systemic inflammatory response, mostly demonstrated by increases in C-reactive protein (CRP) (Peters et al 2001b, Hertel et al 2010, is of major importance in the pathogenesis of cardiovascular events. Upon PM exposure, IL-6 translocates from the lung into the systemic circulation (Kido et al 2011) and is directly involved in the regulation of the synthesis of CRP in the liver. Elevated concentrations of IL-6 are associated with an increased risk of cardiovascular events (Ridker et al 2000, Lindmark et al 2001) and mortality (Volpato et al 2001).…”
Section: Particle Triggered Pathophysiological Mechanismsmentioning
confidence: 99%
“…При этом запускаются процессы окисления липидов и липопротеидов, что ведет к накоплению холесте-рина, а также увеличивает в токе крови количество цитокинов, белков острой фазы, лейкоцитов и тром-боцитов. Данные биохимические нарушения, в свою очередь, способствуют усилению эндотелиальной дис-функции [8]. Итогом такого комплексного воздей-ствия является снижение коронарного резерва, что ведет к прогрессированию проявления ИБС и разви-тию мультифокального поражения артериального русла [9].…”
Section: Discussionunclassified